Abnormal strain evolution of austenite upon martensitic transformation in FeNiCo alloy with invar effect: An in situ study. (November 2022) - Rao, Xiangxiang; Ru, Yadong; Guo, Fangmin; Ren, Yang; Cui, Lishan; Yu, Kaiyuan
Abstract: The lattice strain evolution is essential for the understanding of the invar effect. In this letter, the transformation behavior and lattice strain of austenite in a Fe66 Ni29 Co5 alloy is studied by in situ synchrotron X-ray diffraction during cooling. An abnormal increase of the lattice strain is observed upon martensitic transformation. The strain inhomogeneity is found to increase monotonically before transformation during cooling. The anomalies are suggested to be related to the restricted nature of the transformation, which is further evidenced by the abnormal lattice strain evolution in a laminated Cu/steel nanocomposite. Graphical abstract: Image, graphical abstract